THE INFLUENCE OF CONTENT MARKETING, INFLUENCERS AND PSYCHOLOGICAL FACTORS ON BRAND AWARENESS OF TIKTOK ADVERTISING - Rachelia Fitalia Gumalang; David P. E. Saerang; Fitty Valdi Arie (Universitas Sam Ratulangi, 2022)
The aims of this study is to analyze the Influence of Content Marketing, Influencers and Psychological Factors on Brand Awareness of Tiktok Advertising. The population in this study were students of Sam Ratulangi University. The sampling technique was purposive sampling and obtained 100 respondents that were used as samples. Multiple regression analysis method is used to analyze the effect of the independent variable on the dependent variable. The results showed that partially Content Marketing had no effect on brand awareness of tiktok advertising and Influencers had a significant positive effect on brand awareness of tiktok advertising also psychological factors had a significant positive effect on brand awareness of tiktok advertising. Simultaneously, Content Marketing, Influencers and Psychological Factors have a significant effect on brand awareness of tiktok advertising. Content Marketing are encouraged to always improve their strategies so that they continue to provide the latest breakthroughs and build relationships with customers and potential customers to be able to increase consumer brand awareness.